In Vitro Evaluation of Water and Ethanol Leaf Extracts of Moringa Oleifera Azadirachta Indica and Carica Payaya Against the Growth of Postharvest Fungal Pathogens of Pineapple (Ananas comosus (L) Merr.) - C, Amadioha A.; J, Anidobu R. (Darul Yasin Al Sys, 2024)
Fungi are primary infectious agents of agricultural products that cause significant economic losses of stored food products in Nigeria. Natural plant materials as alternative to synthetic pesticides are eco-friendly, readily available, biodegradable and cost effective. Pathogenicity test of fungal isolates from infected pineapple showed Rhizopus stolonifer, Aspergillus niger and Fusarium solani as pathogenic organisms causing postharvest deterioration of pineapple fruits. The in vitro evaluation of water and ethanol leaf extracts of Moringa oleifera, Azadirachta indica (Neem), and Carica payaya (pawpaw) was carried out to determine the antimicrobial potential of the plant extracts against the spore germination and mycelial radial growth of R. stolonifer, A. niger and F. solani causing rot disease of pineapple in storage. The ethanol and water leaf extracts of A. indica, M. oleifera and C. papaya evaluated as antifungal agents against the three pathogenic fungi in vitro exhibited varying levels of fungitoxicity on the spore germination and mycelia radial growth of the pathogens in culture. The inhibition of spore germination of the pathogens was in a dose dependent manner with 100 % concentration of Neem leaf extract being more potent in inhibiting the spore germination of the pathogens followed by pawpaw and Moringa leaf extracts. The effect of the plant extracts on the mycelia radial growth inhibition of the pathogenic organisms in culture was also concentration dependent with the extracts being more effective from 40% concentration across the test plant materials. However, ethanol leaf extracts were more effective than water extracts in inhibiting the spore germination and mycelia radial growth of the pathogenic organisms in culture indicating that the solvent of extraction affected the fungitoxic activities of extracts of the plant materials with ethanol extracting more active compounds than water as extracting solvent. The antifungal potentials of the test plant materials could be exploited as biopesticide of plant origin in the control of postharvest microbial deterioration of pineapple and sustain the nutritional and market values.